2019
DOI: 10.1016/j.cytox.2019.100009
|View full text |Cite
|
Sign up to set email alerts
|

Milk modulates macrophage polarization in vitro

Abstract: Objective Milk holds an anti-inflammatory response that is particularly important to protecting infants against necrotizing enterocolitis. Milk might also exert anti-inflammatory effects in adulthood, including the oral cavity where macrophages of the oral mucosal control innate immunity defense. It remains unknown, however, whether milk can modulate the local inflammatory response by affecting the polarization of macrophages. Material and Methods To determine whether p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Even though oral mucosal healing was considered the ideal system of wound resolution (Iglesias-Bartolome et al, 2018), oral mucositis is a frequent and severe complication of chemotherapy in children (Cheng et al, 2008) and adults with cancer (Lalla et al, 2014). Considering that milk comes into contact with the oral mucosa, we have recently confirmed TGF-β and antiinflammatory activity of milk in bioassays representing oral fibroblast and oral epithelial cells (Panahipour et al, 2018b(Panahipour et al, , 2019 and macrophages that are highly abundant in the oral mucosa (Panahipour et al, 2018a). We further confirmed the anti-inflammatory activity of regular formula, but not the respective TGF-β activity (Panahipour et al, 2019).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Even though oral mucosal healing was considered the ideal system of wound resolution (Iglesias-Bartolome et al, 2018), oral mucositis is a frequent and severe complication of chemotherapy in children (Cheng et al, 2008) and adults with cancer (Lalla et al, 2014). Considering that milk comes into contact with the oral mucosa, we have recently confirmed TGF-β and antiinflammatory activity of milk in bioassays representing oral fibroblast and oral epithelial cells (Panahipour et al, 2018b(Panahipour et al, , 2019 and macrophages that are highly abundant in the oral mucosa (Panahipour et al, 2018a). We further confirmed the anti-inflammatory activity of regular formula, but not the respective TGF-β activity (Panahipour et al, 2019).…”
Section: Introductionsupporting
confidence: 51%
“…Based on our recent observations that milk has a clear anti-inflammatory activity in primary macrophages (Panahipour et al, 2018a), it was reasonable to investigate whether the findings can be reproduced with RF and HAF. We showed that 1% RF greatly suppressed the saliva-induced inflammatory response in primary macrophages: RF reduced expression of IL-1 and IL-6, with 35.0 and 21.0% expression remaining (median values), respectively, compared with 100% stimulated controls (Figure 5C).…”
Section: Inflammatory Response In Macrophagesmentioning
confidence: 99%
“…12 They also exert regulatory functions with important roles in the control of inflammation and the promotion of healing responses in newborns. 13 Indeed, macrophages are the only cells present in every organ in the body. Macrophages are present in the epidermis, cornea, and the insides of joints, where blood vessels do not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin suppresses extracellular traps released by neutrophils during inflammation [ 68 ], and has also been shown to stimulate pro-inflammatory macrophages (M1) to change to the anti-inflammatory macrophages (M2) type [ 43 , 66 ]. Similarly, pasteurized whole cow’s milk has been shown to polarize macrophages from M1 toward a proresolving M2 phenotype [ 97 ]. In addition, lactoferrin-derived peptides inhibit angiotensin II pro-inflammatory activity through binding to the angiotensin II receptor type 1 [ 69 ], and lactoferrin as well as other peptides in cow’s milk have an antithrombotic effect [ 71 ].…”
Section: Lactoferrin As An Antiviral and Immune Modulatormentioning
confidence: 99%
“…It is further suggested that, in the current circumstances of the COVID-19 pandemic, good quality nonisolated forms of these (such as egg white powder, bovine colostrum powder and other nonultrahigh temperature milk products with appreciable lactoferrin content) should also be tested while ensuring the desired concentrations of each antimicrobial are met, especially in settings where the isolated forms may not be as readily accessible. In favor of this suggestion, studies using lactoferrin-containing milk or lactoferrin-supplemented yoghurt have shown clinical efficacy in viral diseases [ 107 , 178 ], pasteurized whole milk has shown the effect of switching macrophages from M1 to M2 [ 97 ], several peptides in milk are antithrombotic [ 71 ], and several peptides in egg white besides those in ovotransferrin show supportive antioxidant as well as ACE-inhibitory effects [ 79 , 111 ]. However, in those individuals who are already critically ill and on ventilators, more care may need to be taken with the approach.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%